2022
DOI: 10.3390/ani12050538
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and Attitudes of British Residents about the Welfare of Fur-Farmed Species and the Import and Sale of Fur Products in the UK

Abstract: Around 100 million animals are killed annually for the global fur trade, with 85% reared on fur farms and 15% trapped in the wild. Fur farming is banned across the United Kingdom (UK) under the Fur Farming (Prohibition) Act 2000 in England and Wales and parallel legislation in Scotland and Northern Ireland. Despite the farming bans, the import and sale of fur products to the UK have continued, largely due to European Union (EU) membership. The UK left the EU in 2020 and the British government is exploring a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Despite the various fur farming-associated promotional messages and management initiatives, public disapproval for fur production methods largely persists due to the aforesaid problems. For example, in Finland, which has a long history of fur farming, a recent initiative showed strong public support calling on the government to ban commerce (Laatu, 2013), and a UK survey found that approximately four-fifths of respondents opposed the fur industry, and 78% supported a legal prohibition on fur farming (Halliday and McCulloch, 2022).…”
Section: Legal and Governancementioning
confidence: 99%
See 4 more Smart Citations
“…Despite the various fur farming-associated promotional messages and management initiatives, public disapproval for fur production methods largely persists due to the aforesaid problems. For example, in Finland, which has a long history of fur farming, a recent initiative showed strong public support calling on the government to ban commerce (Laatu, 2013), and a UK survey found that approximately four-fifths of respondents opposed the fur industry, and 78% supported a legal prohibition on fur farming (Halliday and McCulloch, 2022).…”
Section: Legal and Governancementioning
confidence: 99%
“…In terms of scale, fur farming involves approximately 85 to 100 million animals annually (Pluda, 2020;Halliday and McCulloch, 2022;Linzey and Linzey, 2022). In comparison, terrestrial livestock farming for protein consumption involves an estimated 74 billion animals annually (Our world in data, 2020).…”
Section: Brief Comparison Of Fur Farming With Livestock Farmingmentioning
confidence: 99%
See 3 more Smart Citations